2007
DOI: 10.1369/jhc.6a7155.2007
|View full text |Cite
|
Sign up to set email alerts
|

Tight Junction Proteins in Gallbladder Epithelium

Abstract: S U M M A R YThere is a paucity of information of tight junction (TJ) proteins in gallbladder epithelium, and disturbances in the structure of these proteins may play a role in the pathogenesis of acute acalculous cholecystitis (AAC) and acute calculous cholecystitis (ACC). Using immunohistochemistry, we investigated the expression of TJ proteins claudin-1, -2, -3, and -4, occludin, zonula occludens (ZO-1), and E-cadherin in 9 normal gallbladders, 30 gallbladders with AAC, and 21 gallbladders with ACC. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…IECs have also the role to produce thymic stromal lymphopoietin (TSLP), IL-2 cytokine member, in response to commensals, such as Gram-negative Escherichia coli or Grampositive Lactobacillus rhamnosous (345). Interestingly it was shown that in patients with Crohn's disease, IECs failed to produce TSLP, with consequent inability to control IL-12, produced by dendritic cells and involved in the development of Thelper 2 cells, resulting in alteration of intestinal homeostasis (346). These dysregulated epithelial-immune cell communication support the evidence of disturbed microbiota in patients with IBD (309).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…IECs have also the role to produce thymic stromal lymphopoietin (TSLP), IL-2 cytokine member, in response to commensals, such as Gram-negative Escherichia coli or Grampositive Lactobacillus rhamnosous (345). Interestingly it was shown that in patients with Crohn's disease, IECs failed to produce TSLP, with consequent inability to control IL-12, produced by dendritic cells and involved in the development of Thelper 2 cells, resulting in alteration of intestinal homeostasis (346). These dysregulated epithelial-immune cell communication support the evidence of disturbed microbiota in patients with IBD (309).…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Our findings extend these prior observations by demonstrating that the effects of moderate changes in Ca 2ϩ concentration on epithelial permeability are due to effects on claudin-2 and, by implication, on the paracellular pathway at the tight junction. Interestingly, both the mammalian gall bladder (33,34) and low resistance strains of MDCK cells such as MDCK II (17) express claudin-2, which likely accounts for the majority of the Na ϩ conductance found by previous investigators to be inhibitable by Ca 2ϩ . However, in our cells, Ca 2ϩ also had similar, albeit lesser, effects on Doxϩ cells that did not express claudin-2 ( Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The pathogenesis of both acute calculous and acalculous cholecystitis (ACC and AAC) is complex and multifactorial: ACC is caused by obstruction of the cystic duct by gallstones, while AAC, representing 2–15% of the cholecystitis, occurs preferentially in critically ill patients [34]. In the gallbladder tissue of AAC patients, only cytoplasmic occludin and Claudin-1 expression is decreased, while ACC patients show a broader downregulation of Claudin-1, Claudin-3, Claudin-4, occludin and ZO1 expression [35]. The broader tight junction alteration observed in patients with ACC can lie in the fact that this pathology results often in a more “local”/gallbladder-centered inflammatory response compared to the systemic inflammatory disease observed in AAC.…”
Section: Tight Junction Disruption As a Consequence Of Cholangiopathies?mentioning
confidence: 99%